2018
DOI: 10.1093/jac/dky083
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of mutations in regulatory genes of resistance-nodulation-cell division efflux pumps in association with tigecycline resistance in Acinetobacter baumannii

Abstract: This study provides an insight into the different mechanisms associated with tigecycline resistance using a genomic approach and points out the importance of considering adeRS and adeN as markers for tigecycline-resistant A. baumannii isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
77
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 41 publications
7
77
1
Order By: Relevance
“…The AdeABC efflux pump was confirmed to export not only tigecycline but also beta-lactam, fluoroquinolone, aminoglycoside and chloramphenicol (Coyne et al, 2011;Xu et al, 2019). As mentioned in previous studies, the overexpression of AdeABC efflux pump has been shown to be related to amino acid substitutions in AdeRS TCS (Gerson et al, 2018;Yoon et al, 2013). Our results indicated that the two amino acid substitutions in AdeRS TCS may be associated to the overexpression of AdeABC efflux pump.…”
Section: Discussionsupporting
confidence: 80%
“…The AdeABC efflux pump was confirmed to export not only tigecycline but also beta-lactam, fluoroquinolone, aminoglycoside and chloramphenicol (Coyne et al, 2011;Xu et al, 2019). As mentioned in previous studies, the overexpression of AdeABC efflux pump has been shown to be related to amino acid substitutions in AdeRS TCS (Gerson et al, 2018;Yoon et al, 2013). Our results indicated that the two amino acid substitutions in AdeRS TCS may be associated to the overexpression of AdeABC efflux pump.…”
Section: Discussionsupporting
confidence: 80%
“…Increased expression can result from mutations in the AdeRS two-component system. In A. nosocomialis M2, the AdeR and AdeS proteins did not contain amino acid substitutions previously associated with increased AdeABC expression (Marchand et al, 2004 ; Yoon et al, 2013 ; Gerson et al, 2018 ). Based on this information, we propose that the AdeABC genes are tightly regulated by AdeRS and the levels of expression in the M2 strain do not contribute to intrinsic resistance.…”
Section: Discussionmentioning
confidence: 70%
“…Tigecycline is an interesting therapeutic option to treat infection by carbapenem-resistant Gram-negative bacteria [ 59 ]. However, the isolates evaluated herein demonstrated resistance to this antimicrobial by the Etest ÂŽ and microdilution methods.…”
Section: Discussionmentioning
confidence: 99%